The use of computer enhanced education: twenty years of dashed hopes (Research, Society and Development, 2022)
The purpose of this article is to present conditions implied in the use of Learning Management Systems (LMS), at the University of Borås (UB), Sweden, specifically in 2004, 2009, 2010, and 2018, highlighting patterns that characterize the routines adopted by the teachers. Utilizing quantitative and qualitative approaches, the exploratory research included the analysis of courses in area of STEM (Science, Technology, Engineering, and Mathematics). In addition to a general analysis of the respective courses, a questionnaire was applied to 76 professors and 926 students from the mentioned courses. The pattern of use is analyzed by means of classification of tools in four groups; distribution tools, communication tools, interaction tools, and course management tools. The results confirm that LMS is widely utilized to distribute documents to students, while the tools facilitating interaction and collaboration are used sparingly and this pattern is consistent over time. Despite an increase in the total use of LMS, there is no increase in the use of digital tools for interaction in Higher Education, which indicates the importance of promoting a wide use of collaborative methods and of encouraging interaction.